ANALYSIS OF DETERMINANTS OF CO2 EMISSIONS IN THE ENERGY SECTOR AS A REFLECTION OF THE GREEN ECONOMY IN INDONESIA, 2000 - 2022 - Ni Komang Noviyanti; Ni Putu Esti Utami Barsua; I Gde Adriyan Antanara (Polytechnic of State Finance STAN, 2024)
Global CO2 emissions are increasing, especially in developing countries such as Indonesia, which is the highest contributor to carbon emissions in ASEAN. This research analyzes the factors that influence CO2 emissions in the Indonesian energy sector from 2000 to 2022. Data from BPS, World Energy, the World Bank, and the Ministry of Energy and Mineral Resources (ESDM) were used to analyze the relationship between CO2 emissions and variables such as GDP, Foreign Direct Investment (FDI), population density, and final energy consumption using multiple linear regression analysis. The findings show that GDP and Final Energy Consumption have a significant relationship with increasing CO2 emissions, while FDI and population density are not statistically significant. However, these two factors still need to be considered in designing future emission reduction policies. The policy recommendations include the adoption of renewable energy, improvements in energy efficiency, and the need for further research to gain a comprehensive understanding of the factors influencing CO2 emissions across different sectors.